2009
DOI: 10.1016/j.ajodo.2007.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution in the temporomandibular joint after mandibular protraction: A 3-dimensional finite element study. Part 2

Abstract: This study indicates that increasing the construction bite height might give more favorable stress patterns in the TMJ, thereby improving the condylar response to functional appliances. The findings of this preliminary study need to be investigated in an animal model and in humans before deriving clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…7,8 This could be attributed to the use of recent version of software with greater sophistication and advanced CAD modeling capabilities. The quality of pattern of stresses in the present study was similar to that in the studies by Gupta et al 7,8 who used IDEAS software and ANSYS 8.0 version, though this study used MIMICS software, which is believed to be more accurate for the CAD modeling procedure along with ANSYS 13.0 version for finite element analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,8 This could be attributed to the use of recent version of software with greater sophistication and advanced CAD modeling capabilities. The quality of pattern of stresses in the present study was similar to that in the studies by Gupta et al 7,8 who used IDEAS software and ANSYS 8.0 version, though this study used MIMICS software, which is believed to be more accurate for the CAD modeling procedure along with ANSYS 13.0 version for finite element analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation to the present study could be that only the left side of TMJ was modeled; thus, all results are based on the characteristics of a single subject. FEM studies in the past 7,8 suggested that increasing construction bite heights was found to generate more favorable stress patterns in TMJ, which could be corelated with a possible improved condylar response to functional appliance treatment. There was availability of an experimental study by Noro et al, 21 wherein the similar hypothesis was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second phase of treatment, fixed orthodontic appliances are used to refine occlusion (1,9). The responses of the temporomandibular joints (TMJs) treated using this method are controversial, which has led to the conduction of studies using the three-dimensional finite element method (10) as well as analyses in groups of experimental animals (11) or humans beings (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%